The Shantu music of the Harims of Nigeria - Mackay, Mercedes (International Library of African Music, 1955)
Perhaps the most fascinating of all Nigerian music is the Shantu music and soft rhythmical singing which comes from the women’s courtyards of the Muslim Harims. I do not know of any other music either in Africa or the world which can be compared to it. Recently I have been able to obtain a tape recording of this music, which is a very difficult thing to come by because the songs themselves are of a very private and intimate nature, and it is impossible for a man to gain access to the women’s quarters. The wife of a student anthropologist managed this however, and I believe that this recording (not very good, alas) is unique.
Keywords: Music; Women; Folk music; Songs; Women musicians; Musical instruments; Hausa (African people); Musicians; Hausa Music; Nigeria; Shantu (Instrument); African Music